Mutual influence of selenium nanoparticles and FGF2-STAB® on biocompatible properties of collagen/chitosan 3D scaffolds: in vitro and ex ovo evaluation - Muchová, Johana; Hearnden, Vanessa; Michlovská, Lenka; Vištejnová, Lucie; Zavaďáková, Anna; Šmerková, Kristýna; Kočiová, Silvia; Adam, Vojtěch; Kopel, Pavel; Vojtová, Lucy (BioMed Central Ltd, 2021)
In a biological system, nanoparticles (NPs) may interact with biomolecules. Specifically, the adsorption of proteins on the nanoparticle surface may influence both the nanoparticles' and proteins' overall bio-reactivity. Nevertheless, our knowledge of the biocompatibility and risk of exposure to nanomaterials is limited. Here, in vitro and ex ovo biocompatibility of naturally based crosslinked freeze-dried 3D porous collagen/chitosan scaffolds, modified with thermostable fibroblast growth factor 2 (FGF2-STAB®), to enhance healing and selenium nanoparticles (SeNPs) to provide antibacterial activity, were evaluated. Biocompatibility and cytotoxicity were tested in vitro using normal human dermal fibroblasts (NHDF) with scaffolds and SeNPs and FGF2-STAB® solutions. Metabolic activity assays indicated an antagonistic effect of SeNPs and FGF2-STAB® at high concentrations of SeNPs. The half-maximal inhibitory concentration (IC50) of SeNPs for NHDF was 18.9 µg/ml and IC80 was 5.6 µg/ml. The angiogenic properties of the scaffolds were monitored ex ovo using a chick chorioallantoic membrane (CAM) assay and the cytotoxicity of SeNPs over IC80 value was confirmed. Furthermore, the positive effect of FGF2-STAB® at very low concentrations (0.01 µg/ml) on NHDF metabolic activity was observed. Based on detailed in vitro testing, the optimal concentrations of additives in the scaffolds were determined, specifically 1 µg/ml of FGF2-STAB® and 1 µg/ml of SeNPs. The scaffolds were further subjected to antimicrobial tests, where an increase in selenium concentration in the collagen/chitosan scaffolds increased the antibacterial activity. This work highlights the antimicrobial ability and biocompatibility of newly developed crosslinked collagen/chitosan scaffolds involving FGF2-STAB® and SeNPs. Moreover, we suggest that these sponges could be used as scaffolds for growing cells in systems with low mechanical loading in tissue engineering, especially in dermis replacement, where neovascularization is a crucial parameter for successful skin regeneration. Due to their antimicrobial properties, these scaffolds are also highly promising for tissue replacement requiring the prevention of infection.

In a biological system, nanoparticles (NPs) may interact with biomolecules. Specifically, the adsorption of proteins on the nanoparticle surface may influence both the nanoparticles' and proteins' overall bio-reactivity. Nevertheless, our knowledge of the biocompatibility and risk of exposure to nanomaterials is limited. Here, in vitro and ex ovo biocompatibility of naturally based crosslinked freeze-dried 3D porous collagen/chitosan scaffolds, modified with thermostable fibroblast growth factor 2 (FGF2-STAB®), to enhance healing and selenium nanoparticles (SeNPs) to provide antibacterial activity, were evaluated. Biocompatibility and cytotoxicity were tested in vitro using normal human dermal fibroblasts (NHDF) with scaffolds and SeNPs and FGF2-STAB® solutions. Metabolic activity assays indicated an antagonistic effect of SeNPs and FGF2-STAB® at high concentrations of SeNPs. The half-maximal inhibitory concentration (IC50) of SeNPs for NHDF was 18.9 µg/ml and IC80 was 5.6 µg/ml. The angiogenic properties of the scaffolds were monitored ex ovo using a chick chorioallantoic membrane (CAM) assay and the cytotoxicity of SeNPs over IC80 value was confirmed. Furthermore, the positive effect of FGF2-STAB® at very low concentrations (0.01 µg/ml) on NHDF metabolic activity was observed. Based on detailed in vitro testing, the optimal concentrations of additives in the scaffolds were determined, specifically 1 µg/ml of FGF2-STAB® and 1 µg/ml of SeNPs. The scaffolds were further subjected to antimicrobial tests, where an increase in selenium concentration in the collagen/chitosan scaffolds increased the antibacterial activity. This work highlights the antimicrobial ability and biocompatibility of newly developed crosslinked collagen/chitosan scaffolds involving FGF2-STAB® and SeNPs. Moreover, we suggest that these sponges could be used as scaffolds for growing cells in systems with low mechanical loading in tissue engineering, especially in dermis replacement, where neovascularization is a crucial parameter for successful skin regeneration. Due to their antimicrobial properties, these scaffolds are also highly promising for tissue replacement requiring the prevention of infection.
Mutual influence of selenium nanoparticles and FGF2-STAB® on biocompatible properties of collagen/chitosan 3D scaffolds: in vitro and ex ovo evaluation
Keywords: 3D porous scaffold; Chitosan; Collagen; Fibroblast growth factor 2; Selenium nanoparticles; 3D porous scaffold; Chitosan; Collagen; Fibroblast growth factor 2; Selenium nanoparticles